2005
DOI: 10.1051/vetres:2005022
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella in sows: a longitudinal study in farrow-to-finish pig herds

Abstract: -Besides finishing pigs, sows are also believed to be important in the epidemiology of Salmonella. The study objective was to investigate the prevalence of Salmonella excretion in sows during an entire reproductive cycle. In 3 farrow-to-finish herds, groups of 34, 40 and 32 sows, respectively, were sampled serially. Faecal samples, environmental swabs and feed samples were taken and submitted to a qualitative Salmonella isolation. All isolates were characterised using RAPD and a representative number of isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 33 publications
13
37
0
1
Order By: Relevance
“…This analysis of Salmonella status in the latently infected farrow-to-finish herds corresponds with the findings of other authors (Nollet et al 2005;Farzan et al 2007;Rajic et al 2007) who demonstrated a low correlation between seropreva-lence of specific Salmonella antibodies and their isolation from swine faeces. The presence of high titre of specific antibodies does not always signify infection, but is indicative of previous exposure.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This analysis of Salmonella status in the latently infected farrow-to-finish herds corresponds with the findings of other authors (Nollet et al 2005;Farzan et al 2007;Rajic et al 2007) who demonstrated a low correlation between seropreva-lence of specific Salmonella antibodies and their isolation from swine faeces. The presence of high titre of specific antibodies does not always signify infection, but is indicative of previous exposure.…”
Section: Discussionsupporting
confidence: 90%
“…Breeding pigs, predominantly sows, may be an important source of dissemination of Salmonella throughout the pig production chain. After farrowing, faecal shedding of Salmonella increases in sows, contaminating pens and the environment which creates potential sources of infection for piglets (Nollet et al 2005). A direct relationship has been confirmed between breeder pig herd Salmonella prevalence in faeces (above 100) and findings of the same serotypes in ileocaecal lymph nodes and swabs from carcasses of fattening pigs at slaughter.…”
Section: Discussionmentioning
confidence: 81%
“…This information complements existing evidence, indicating that Salmonella spp. infection can occur in young pigs (Nollet et al, 2005a;Griffith et al, 2006). The percentage of seropositive piglets (48.8%) at 21 AE 3 days old may reflect the passive immune protection against Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%
“…The association between stress and Salmonella spp. excretion has been previously described (Kranker et al, 2003;Nollet et al, 2005a;Griffith et al, 2006). Although there is no information about the degree of impact of transportation and commingling of litters, in three separate sites with all-in=all-out management systems, it was determined that transportation and litter commingling should be diminished to reduce Salmonella spp.…”
Section: Salmonella Pigs Serology Pfge and Multidrug Resistancementioning
confidence: 99%
“…Es por esto que estos tratamientos en la actualidad son poco efectivos, como por ejemplo el uso de amoxicilina en personas 29 . Según el análisis exploratorio observado en la construcción del MCA, la variabilidad de el origen alimentario y animal indica que la mantención y diseminación de cepas resistentes se explicaría por factores como sistemas de producción, manejos de tratamientos antibióticos, contacto con reservorios naturales, entre otros 30,31 . Los valores de CMI que superan los niveles mí-nimos de interpretación de resistencia antibiótica, se relacionan con la expresión de ciertas enzimas que deben ser detectadas mediante estudios moleculares 32 .…”
Section: Discussionunclassified